NMR diffusion measurements of complex systems - Stait-Gardner, Tim; Willis, Scott A.; Yadav, Nirbhay N.; Zheng, Gang; Price, William S. (Diffusion Fundamentals, 2009)
The pulsed gradient spin-echo nuclear magnetic resonance experiment is a powerful tool for studying the constitution and structure of complex systems (e.g., polydisperse systems and porous media). In applications to polydisperse systems, it is important to consider the effects of obstruction, exchange, entanglement, and diffusional averaging processes whereas in applications to porous samples, reliable structural information can only be extracted from the time-dependence of the apparent diffusion coefficient when the deleterious effects of spatially and/or temporally inhomogeneous background (magnetic field) gradients can be suppressed. These issues are considered in this review.